Bitter Taste in the Treatment of Heart Diseases from Avicenna's Point of View - Maryam Mohammadi-Araghi; Malihe Tabarrai; Arman Zargaran; Fatemeh Nejatbakhsh (Tehran University of Medical Sciences, 2024)
The function of bitter taste due to the existence of too much of its receptor on many extra-oral tissues is not only related to the oral cavity, but is effective in many physiological functions. More than ten centuries ago, Avicenna (980-1032 CE), a Persian physician, pointed to the effects and functions of various tastes in the body. In this research, we examined the heart medicines mentioned by Avicenna, relying on their taste, especially the bitter taste.  The books used in the case of Persian Medicine included the following: Qanun Fi al-Teb (Canon of Medicine), Manafe-al-Aghzieh va Daf-e-Mazareha and Treatise on Cardiac Drugs. In addition, articles published in English in the last 10 years were searched in PubMed, Google Scholar, Scopus and Embase. Vasodilation, inotropic effects, cardio-protection, digital like effect, reducing the accumulation of calcium and nitric oxide in the heart, antioxidant activity, improving heart metabolism and preserving mitochondrial function after MI are some of the cardiovascular effects of Avicenna`s bitter tasting heart medicines, which are also confirmed by clinical evidences in modern investigations. The findings of this research show that the function of bitter-tasting herbal drugs in the body can have beneficial cardiovascular effects, some of which  have been proven in studies, and more researches is needed in this field.